RECYCLING OF FERROUS METAL SHAVINGS - S. L. Rovin; L. E. Rovin; T. M. Zayac; O. M. Valickaya (Литьë и металлургия, 2018)
The most advanced and universal way of chips recycling of ferrous metals is the technology of direct chips remelting in rotational tilting furnaces (RBF) directly at the enterprises-sources of waste generation. However common practice of iron and steel chips recycling is based on its briquetting and subsequent remelting in traditional furnaces.For cost reduction when chip briquetting and organization of hot briquetting sections in places of its formation highly efficient equipment – rotational dryer and RBF is proposed. The possibility and effectiveness of developed furnaces for lowand high-temperature chip heating in briquetting lines is proved. Thermal efficiency of such furnaces when dispersed materials heating is much higher than drum or feed-through furnaces. Hot briquetting of shavings reduces the pressing force, which reduces the specific energy consumption. The use of rotary kilns can reduce technological operations and equipment of production sites for the manufacture of briquettes